Radical 1, 2-aryl migration in α, α-diaryl allylic alcohols toward β-silyl ketones1. Issue 41 (7th November 2015) - Peng, Haibo; Yu, Jin-Tao; Jiang, Yan; Cheng, Jiang
<x xml:space="preserve">Abstract</x> A copper-catalyzed radical 1, 2-aryl migration in α, α-diaryl allylic alcohols is developed, leading to β-silyl carbonyl compounds in moderate to good yields.